PENGARUH USIA DAN KONSEP DIRI TERHADAP PENCAPAIAN PERAN IBU SAAT BAYI USIA 0-6 BULAN DI DESA BOJONGSARI, KECAMATAN BOJONGSARI, KABUPATEN PURBALINGGA - Oktafiani, Senti; Fajarsari, Dyah; Mulidah, Siti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Age impacts a mother's experience to achieve psychological maturity, so does self- concept, a good self-concept also gives good impacts on the achievement was of a motherâ€™s role. The research objectived to find the influence of age and self-concept tothe achievement of motherâ€™s role when her baby was 0-6 months old in Bojongsari village, Bojongsari districts, Purbalingga regency.This research used the analytical method with cross sectional approach. The population in this research were the motherâ€™s whose their babies were > 6 months to a year old in the Bojongsari village with population of 79 people. The sampling technique usedsimple random sampling with 44 samples of respondents. The univariate analysis used the frequention distribution and bivariate analysis used the test of rank spearman. The known research result most of the mothers who was 20-35 years old (54.5%), the mother did not work (56.8%) more than the mother work (43.2%), both good and less good self-concept was equivalent (50.0%). The role of mother achievement that unfavorable was more (52.3%) than good (47.7%). The role achievement of mothers who are not working (52,0%)Â  better than those who are workingÂ  (18.2%). There was an influence ofÂ  age and self-concept to the achievement of mothers role when her baby were 0-6 months old in Bojongsari village, Bojongsari Districts, Purbalingga regency in 2013.(Ï = 0.008) and (Ï = 0.000). There was an influence of age and self-concept to the achievement of mothers role when her baby 0-6 months old in Bojongsari village, Bojongsari districts, Purbalingga regencyin 2013 Keywords : Age, Self Concept, Achievement Mother Role